Analysis of mean transcutaneous capnography in consecutive patients undergoing polysomnography - Giulio Cesare Pinnola; Patrícia Souza Bastos (Arquivos de Neuro-Psiquiatria)
Transcutaneous capnography is a noninvasive method useful for analysis of the behavioral tendency of transcutaneous CO2 pressure (PtcCO2) in patients undergoing polysomnography, to evaluate respiratory sleep disorders. Objective Determine normative PtcCO2 values in normal patients undergoing polysomnography. Method One hundred seventy-nine patients who underwent polysomnography with simultaneous PtcCO2 measurement were assessed by means of a transcutaneous capnograph (TCM4 series from Radiomiter). Results The group classified as normal (N=53) presented a apnea/hypopnea index (AHI) <5 events/per hour of sleep and their age groups varied between 7 and 76 years of age. Conclusion Global mean values of PtcCO2 in the normal group had a Gaussian distribution that varied between 33.1 and 50.0 mmHg (SD 4,363). Such findings allowed the establishment of normative PtcCO2 values for normal individuals.